Biochemical Markers and Uterine Artery Doppler Study for the Prediction and the Severity of the Hypertensive Disorders during Pregnancy (Global Journal of Medical Research, 2017)
Hypertensive disorder in pregnancy (HDP) is one of the major cause of maternal and perinatal mortality & morbidity worldwide particularly in developing countries. In developed countries, maternal mortality rate varies from 4-40 per 1 lakh live birth. In developing countries, it varies from 100-700 with India having 178 per 1 lakh live birth. Objective: Study of biochemical markers and uterine artery Doppler for the prediction of hypertensive disorders and its severity. Sensitivity and Specificity of biochemical markers and Uterine Artery Doppler and their comparison for the prediction and the severity of hypertensive disorders during pregnancy. Material & Methods - This is a prospective study. Approximately hundred patients with hypertensive disorders during pregnancy attending the OPD (Out patients Department) and IPD (In patient Department) in Obstetrics & Gynecology department will be included. All the patients in this study group will be subjected to biochemical markers tests and Ultrasonographic evaluation of the pregnancy along with the Arterial Doppler of both the Uterine Artery and Umbilical Artery will be done. Conclusion: Using biochemical markers (Inhibin-A and PAPP-A) and Uterine Artery Doppler Study in combination is significantly useful in early prediction of PIH having specificity and sensitivity of Inhibin-A as 88.89% and 83.33%, PAPP-A as 89.29% and 71.43%, Uterine artery Doppler study – Pi Index as 91.67% and 85.71 %, Ri Index as 87.5% and 71.43% and diastolic notch as 94.44% and 92.85 % respectively. The use of biochemical markers and uterine artery Doppler Study as an important tool for early prediction of PIH and has a lot of prognostic value.
Keywords: hypertension; hypertensive disorder in pregnancy; biochemical markers; uterine artery doppler